Hubungan Peran Guru Terhadap Motivasi Belajar Penjas Pada Masa Pandemik Covid-19 di SMP Negeri 2 Rawamerta - Yogi Listiano; Akhmad Dimyati; Muhammad Mury Syafei (Peneliti.net, 2021)
This study aims to determine the relationship between the teacher's role and the motivation to learn physical education at SMP Negeri 2 Rawamerta. The method used in this research is a survey using correlational expos facto. The population used in this study were 207 students of SMP 2 Rawamerta class VIII, the samples used in this study were 41 students of class VIII D and physical education teachers of SMP Negeri 2 Rawamerta. The sampling technique used in this study is cluster random sampling. The instrument used in this research is a questionnaire aimed at students. The statistical analysis used in this study is the product moment correlation with the hypothesis that if t count < t table (0.007 < 0.05) then Ho is rejected, meaning that the research shows that there is a relationship between the teacher's role on physical education learning motivation at SMP Negeri 2 Rawamerta.